Pengembangan Media PADASIA (Peta Budaya Indonesia) Pada Mata Pelajaran Ilmu Pengetahuan Sosial Bagi Siswa Kelas IV SD - Mir’atun Nisa’; Arya Setya Nugroho (Departement of Mathematics Education, 2023)
Media as a vehicle for distributing information or knowledge as a messenger. and the learning process because presenting the media as an intermediary can alleviate the ambiguity of the subjects in these learning activities. Media can represent what the teacher is unable to convey in front of the class, making it easier for students to understand lessons compared to without media. This research is a development research aimed at producing learning media in the form of a map of Indonesian culture. This research was conducted using a 4-D research type. The subjects of this study were fourth grade students at SDN 42 Gesik. The techniques used for data collection were media expert validation questionnaires, material expert validation questionnaires, and student response questionnaires. The results of the validation of media experts obtained 90% and material experts reached 93.75%, both of which indicated the